Factor Influencing Mortality in Moderate - Severe Covid-19 Patients In Tertiary Hospital, Indonesia - Faried, Mukhamad; Ginting, Franciscus; Kembaren, Tambar; Eyanoer, Putri Chairani (Journal of Society Medicine, 2023)
Introduction: Covid-19 is highly contagious respiratory tract infection caused by infection of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). This infection has a case fatality rate in those with moderate – severe case up to 30%. This study aims to analyse factor influencing mortality in moderate to severe Covid-19. Method: This study was conducted using retrospective cohort study on moderate - severe Covid-19 patients who were treated in tertiary hospital in Medan, Indonesia, in March 2020-June 2022. Results: From 180 moderate – severe Covid-19 inpatients, up to 37,8% died. Factor that influences the mortality is the presence of comorbidity (P=0,001), such as hypertension and chronic kidney disease (CKD), high levels of neutrophil-lymphocyte Ratio (NLR), procalcitonin, c-reactive protein (CRP), D-dimer, and low levels of albumin with P values 0,016, 0,036, 0,001, 0,001, 0,001, 0,003, and 0,006 consecutively. Conclusion: It can be concluded that the demographic factors that are significantly related to the death of Covid-19 patients are the presence of comorbidities such as hypertension and CKD.